1997
DOI: 10.1590/s0037-86821997000500001
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of strongyloidosis in patients with hematologic malignancies

Abstract: Recebido para publicação em 16/12/96 Revista da Sociedade Brasileira de Medicina Tropical 30(5):355-357, set-out, 1997.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 15 publications
0
14
0
3
Order By: Relevance
“…In a prospective study conducted in patients with hematologic malignancies, the prevalence was 8.3%, a result similar to ours. 22 In our study, a selection bias could be present since the mean number of stools examined in infected patients was two, less than the three required by the patient to be considered not infected. Only 64% of the patients had three stool samples examined and some of the other 36% (101 patients) could be undiagnosed.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…In a prospective study conducted in patients with hematologic malignancies, the prevalence was 8.3%, a result similar to ours. 22 In our study, a selection bias could be present since the mean number of stools examined in infected patients was two, less than the three required by the patient to be considered not infected. Only 64% of the patients had three stool samples examined and some of the other 36% (101 patients) could be undiagnosed.…”
Section: Discussionmentioning
confidence: 74%
“…21,22 The number of patients required to estimate a 95% confidence interval for the specificity of the test of 88% was 162. The number of control patients selected to perform the cutoff calculation was determined in the same way, except that the estimated prevalence of strongyloidiasis (98%) was taken from the specificity of a ELISA in immunocompetent patients.…”
Section: Patients Materials and Methodsmentioning
confidence: 99%
“…[29][30][31][32]34 However, these series are of limited reliability because in some cases the presence of eosinophilia was a determinant factor for examining the stool samples of infected individuals, while other studies were conducted in patients with hematologic disease or in individuals reporting to a hospital for non-specified reasons and who may have had pathologic processes implying eosinophilia. In our study, based on a population of farm workers, the presence of eosinophilia was found to be a satisfactory indicator of infection, resulting in good sensitivity and excellent specificity.…”
Section: Discussionmentioning
confidence: 99%
“…However, in immunocompromised hosts S. stercoralis may cause a frequently fatal hyperinfection or disseminated disease 11 . Many cases of strongyloidiasis were described among a variety of conditions of immunosuppression, especially impairment of cell-mediated immunity, such as hematologic malignancies 10,19 , lymphoma 21 , renal transplantation 9 and HIV + (human immunodeficiency virus infection) 8 .…”
mentioning
confidence: 99%